OPTIMALISASI FUNGSI SATUAN INTELIJEN KEAMANAN DALAM PENYELIDIKAN TINDAK PIDANA NARKOTIKA YANG DILAKUKAN OLEH ANGGOTA POLRI - Desra Handika (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
There are several members or personnel who abuse narcotics. This is evidenced by the large number of information reports reported by the Intelligence and Security Unit (Sat Intelkam) of the Pagar Alam Police. Investigations carried out by the Intelligence and Security unit (Sat Intelkam) of the Pagar Alam Police often encounter various obstacles, this is mainly because the perpetrators are also members of the police themselves. The existence of a sense of loyalty among fellow members is one of the obstacles in the investigation process. The problem in this research is how to optimize the function of intelligence in the investigation of narcotics crimes by members of the Pagar Alam Resort Police and how the obstacles faced by police intelligence in investigating narcotics crimes are carried out. Member of the Pagar Alam Resort Police. In this study using empirical normative legal research methods with approaches to legislation (Statute Approach) and conceptual approach (conceptual approach). The data collection in this study was carried out by means of library research on the relevant laws and regulations and analyzing the data qualitatively. The results of this research concluded that the function of the National Police Intelligence in investigating members of the Police who commit narcotics crimes is to seek, explore, and collect data as complete as possible from various sources, both open and closed sources through activities that are also open or closed, then the data is processed into intelligence products, namely information that is ready to be used as the basis for making decisions or actions. These constraints are law enforcement factors that result in delays in law enforcement against narcotics crimes committed by the police. The Police must take action against their members who commit crimes, not to protect their members who are involved in narcotics crimes